Análisis de la legislación de los patrimonios autónomos desde una perspectiva económica, a propósito de los últimos cambios a la normativa sobre titulización de activos - Castritius Mendoza, Paul (2023)
This article, based on the analysis of the economic effects of the main aspects of the Modification, Securitization Regulation, provides an overview of the status of the legislation of autonomous assets, reviewing how the initial design of such legislation, whose purpose was to lay the foundations for the development of such estates, nonexistent at that time, has been changing over time, and what are the general effects of such changes. Also, it formulates some proposals for a general modification of the current design of such legislation, with the purpose of creating a more efficient system for the benefit of the agents of the economy.